PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA PAREPARE - Arifin, Arman (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
The study is intended to gain evidence of the impact of reward and punishment on employee performance in the Secretariat Parepare Office. The data-collection techniques used in this study are questionnaires. The samples in this study number 88. Data analysis techniques in this study use computerized system analysis techniques. Partial research obtained value t count = 2.388 and its tabled t known = 1.98827 and its importance = 0.019 < 0.5. Reward (X1) affected positive and significant (Y). Simultaneously reward (X1), punishment (X2) has a positive and significant impact on employee performance (Y), which F count is 6,098 and the value of the table is 3,10, which 6,098 > 3,10.